2003
DOI: 10.1080/1071576021000036614
|View full text |Cite
|
Sign up to set email alerts
|

PON1 Paraoxonase Activity is Reduced During HDL Oxidation and is an Indicator of HDL Antioxidant Capacity

Abstract: The aim of this study was to investigate the effect of HDL oxidation on PON1 paraoxonase activity. Also, we were interested in investigating the mechanism by which PON1 could be inactivated and the correlation between its enzymatic activity and the antioxidant properties of HDL. Three different oxidation systems were used for the HDL oxidation: (1) oxidation induced by THP1 cells, (2) oxidation induced by copper ions at a concentration 10 microM, and (3) oxidation induced by *OH and O2.- oxygen free radicals p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 28 publications
5
54
1
2
Order By: Relevance
“…5) Van Lenten et al, 2001b). Furthermore, decreased PON1 activity may be caused by enzyme inactivation as a result of oxidation (Jaouad et al, 2003) and/or glycation (Hedrick et al, 2000;Ferretti et al, 2001). Consistent with these observations, serum concentrations of PON1 are decreased in subjects with MetS (Blatter Garin et al, 2005) and in patients with type 1 and type 2 diabetes (Boemi et al, 2001;Costa et al, 2005), who feature elevated levels of inflammation and oxidative stress (Ridker et al, 2004a).…”
Section: A Altered High-density Lipoprotein Composition and Enzymatisupporting
confidence: 68%
“…5) Van Lenten et al, 2001b). Furthermore, decreased PON1 activity may be caused by enzyme inactivation as a result of oxidation (Jaouad et al, 2003) and/or glycation (Hedrick et al, 2000;Ferretti et al, 2001). Consistent with these observations, serum concentrations of PON1 are decreased in subjects with MetS (Blatter Garin et al, 2005) and in patients with type 1 and type 2 diabetes (Boemi et al, 2001;Costa et al, 2005), who feature elevated levels of inflammation and oxidative stress (Ridker et al, 2004a).…”
Section: A Altered High-density Lipoprotein Composition and Enzymatisupporting
confidence: 68%
“…There are two possible mechanisms for the substrate-dependent alteration of PON1 activity: one is that PON1, modified by acquired factors such as reactive oxygen species or reactive aldehydes, may distinguish between two substrates, phenyl acetate and paraoxon; the other is that paraoxonase and arylesterase activities may be discriminated by endogenous inhibitors, which are present in the HDL particle or se- rum sample. Earlier studies have shown that PON1 could be inactivated by endogenously generated oxidants (12,14,31,32,48). In the present study, however, the differential substrate recognition was not addressed by any PON1 molecules modified by the oxidants except HOCl, which caused a greater reduction of arylesterase activity than paraoxonase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the oxidative inactivation of PON1, it has been shown that PON1 activity was reduced during exposure to oxidized LDL or reactive oxygen species (28)(29)(30)(31)(32). Additionally, 4-hydroxy-2-nonenal, which gradually accumulates in the later stage of LDL oxidation, can also cause the inactivation of PON1 arylesterase activity (32).…”
mentioning
confidence: 99%
“…There are several reports about oxidative inactivation of paraoxonase (Cao et al 1999, Jaouad et al 2003.…”
Section: Pon1 Activitymentioning
confidence: 99%